Impact of Depression on Progression of Impairment and Disability in Early Parkinson's Disease. Issue 4 (14th July 2015) - Bega, Danny; Luo, Sheng; Fernandez, Hubert; Chou, Kelvin; Aminoff, Michael; Parashos, Sotirios; Walker, Harrison; Russell, David S.; Christine, Chadwick W.; Dhall, Rohit; Singer, Carlos; Bodis‐Wollner, Ivan; et al.
Abstract: Background: Depression is one of the most common nonmotor symptoms associated with Parkinson's disease (PD), yet the impact of depression on progression of disease is unclear. Objective: The aim of this study was to prospectively characterize the relationship between depressive symptoms and measures of disease progression in a large sample of patients with early, medically treated PD. Methods: Baseline and longitudinal Beck Depression Inventory (BDI) scores from participants in the NINDS Exploratory Trials in PD Long Term Study 1 were correlated with changes in multiple measures of disease severity over 5 years. Multivariate analysis of predictors of change in BDI was performed. Results: Of 1, 741 participants, 746 completed 5‐year assessments and were included. Mean age was 62.00 years (standard deviation [SD]: 9.22) and mean disease duration was 1.69 years (SD, 1.16). Mean BDI score was 6.24 (SD, 5.02) at baseline and 8.57 (SD, 6.60) at 5 years. Baseline BDI score was strongly associated with rate of change in all examined measures of disease severity. In multivariate analysis, BDI 5‐year change was associated with change in UPDRS Part I (excluding depression item; P  < 0.01), 33‐item Parkinson's Disease Questionnaire ( P  < 0.01), EuroQOL Five Dimensional Questionnaire ( P  = 0.02), and Total Functional Capacity ( P  < 0.01), but was not associated with motor or cognitive measures. This model explained 68.8% of the variance 5‐year change of the BDI score. Conclusions: Worse baseline BDI scores are associated with a decline in multiple measures of disease severity in PD. Worsening of BDI at 5 years was associated with worsening in UPDRS Part I and quality‐of‐life measures, but not with motor or cognitive measures.